Low haemoglobin is associated with increased risk of complications in left atrial appendage closure patients. (14th October 2021) - Zweiker, D; Sieghartsleitner, R; Toth, G; Stix, G; Vock, P; Schratter, A; Fiedler, L; Aichinger, J; Steinwender, C; Binder, R.K; Barbieri, F; Ablasser, K; et al.
Abstract: Introduction: Left atrial appendage closure is associated with a relevant procedural complication rate. Baseline risk factors, such as pre-procedural lab results, may identify patients that develop acute complications. Methods: We performed a retrospective analysis of the impact of baseline characteristics and preprocedural lab results on the acute procedural outcome in patients undergoing left atrial appendage closure from the Austrian Left Atrial Appendage Closure Registry between 2010 and 2019. The endpoint for procedural complications was defined as death, stroke, major bleeding, necessity for intensive care, other complications requiring invasive interventions or failure to implant the device. We also evaluated a modified endpoint with the exclusion of bleeding events. Logistic regression was performed using stepwise approach (backward method with p_out = 0.1) and forced inclusion of age, left-ventricular function and kidney function. Results: A total of 320 consecutive patients from 9 centres with a median age of 75 years (36.6% female) were included. Seventy-eight percent had a history of bleeding and 35% had a history of stroke. Median CHA2DS2-VASc score was 5 (interquartile range, 3–5) and median HAS-BLED score was 3 (2–4). Procedural complications occurred in 15.3% of cases. Low haemoglobin and low activated partial thromboplastin time were associated with an increased complication rate. Other significant baseline factors were liver disease, absence of intracranial haemorrhage and severe aortic stenosis. In multivariate analysis, low haemoglobin remained a significant predictor, even after adjustment for age, left-ventricular function and kidney function (Table). In the modified procedural complication endpoint excluding major bleeding events (14.1%), low haemoglobin remained a significant predictor (haemoglobin 11.9±2.0 vs. 12.8±2.0 g/dL in patients with vs. without modified endpoint, p=0.013). A baseline haemoglobin lower than 12 g/dL was present in 39.4% and it increased relative risk of procedural complications by 89% (21.4 vs. 11.3% in patients with reduced vs. normal haemoglobin), and risk of complications without bleeding by 92% (19.8 vs. 10.3%). Conclusion: Low baseline haemoglobin is independently associated with a higher complication rate after left appendage closure compared to patients with normal haemoglobin levels, even in a modified endpoint excluding bleeding and requirement for transfusion. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boston Scientific - unrestricted grant